COMPLIANCE WITH TREATMENT OF NON-COMMUNICABLE DISEASE PATIENTS (NCDs) WITH A COLLABORATIVE INTERPROFESSIONAL APPROACH IN THE AREA OF THE LEBAK DISTRICT HEALTH CENTER - Suhartini; Ahmad (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Non-communicable diseases require long treatment and medication, thus impacting patient compliance in taking medication. Patient medication compliance is an important factor in the management of Non-communicable diseases. The study aims to determine the effect of the Collaborative Interprofessional Approach model on medication compliance of Non-communicable Disease patients in Community Health Centers. The research method is a mix method cross-sectional survey design on patients and quasi-experimental on health workers with the form of collaborative interprofessional training interventions and the provision of monitoring books for Non-communicable Disease patients, with a sample size of 159 patients and 64 health workers. The results of the study showed a relationship between age and medication compliance of non-communicable disease patients with a p value = 0.03. There was a relationship between patients with family members suffering from non-communicable diseases and medication adherence in those with non-communicable diseases (p=0.003). There was a relationship between the use of a non-communicable disease monitoring book and medication adherence in those with non-communicable diseases (p=0.000 and OR=4.737). There was an increase in staff knowledge before and after training on the use of interprofessional education books. It can be concluded that the use of medication adherence books and the IPE-C approach are effective in the care and control of non-communicable diseases.